Electric field changes generated by the preliminary breakdown for the negative cloud-to-ground lightning flashes in Malaysia and Sweden - Baharudin, Zikri Abadi (Elsevier, 2012)
We present the study of the electric field changes generated by the preliminary breakdown for negative cloud-to-ground lightning flashes in Malaysia and Sweden concerning the association of slow field changes associated in preliminary breakdown process. We examined the total of 1685 negative cloud-to-ground lightning flashes from the total of 39 thunderstorms by recording the slow electric field, fast electric field and narrowband radiation field at 3 and 30 MHz signals simultaneously. Our results show that there is a pre-starting time, i.e. the duration between the first preliminary breakdown pulse and slow field changes starting point, which is found to be after the first preliminary breakdown pulse. The pre-starting time has the arithmetic mean and geometric mean range from 1.4 – 6.47 and 1 – 3.36 ms, respectively. The mean values of pre-starting time in Malaysia are greater than the values observed in Sweden by more than a factor of 3. From the two data sets show that the slow field changes never start before the preliminary breakdown. Furthermore, the use of single-station electric fields measurement with high resolutions of 12 bits transient recorder with several nanosecond accuracy allow one to distinguish the slow field changes generated by preliminary breakdown, which preceded the negative first return stroke, between tens to hundreds of milliseconds of pre-return stroke duration.